2013
DOI: 10.1016/j.ejmech.2013.03.064
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminobenzothiazole derivatives: Search for new antifungal agents

Abstract: a b s t r a c tA new series of 6-substituted 2-aminobenzothiazole derivatives were synthesized and screened in vitro as potential antimicrobials. Almost all the compounds showed antifungal activity. In particular, compounds 1n,o, designed on the basis of molecular modeling studies, were the best of the series, showing MIC values of 4e8 mg/mL against Candida albicans, Candida parapsilosis and Candida tropicalis. None of the two compounds did show any cytotoxicity effect on human THP-1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 35 publications
1
68
0
1
Order By: Relevance
“…For instance, 2-mercapto derivatives were generally more active against bacteria, while the 2-amino ones were more potent against fungi. This emphasizes the importance of the substitution withbulky groups at the 6-position of the 2-aminobenzothiazole moiety for enhancing antifungal activity [72].…”
Section: Bta As Antimicrobial Agentsmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, 2-mercapto derivatives were generally more active against bacteria, while the 2-amino ones were more potent against fungi. This emphasizes the importance of the substitution withbulky groups at the 6-position of the 2-aminobenzothiazole moiety for enhancing antifungal activity [72].…”
Section: Bta As Antimicrobial Agentsmentioning
confidence: 98%
“…Compounds (72,73) polymerization and immuofluorescence analysis showed that these compounds effectively inhibit microtubule assembly at both, molecular and cellular levels, in A549 cells [115]. 2-Phenyl BTA linked imidazole moiety were prepared and evaluated for anticancer activity against different human cancer cells.…”
Section: Bta As Microtubule Polymerization Inhibitorsmentioning
confidence: 99%
“…The target thienopyrimidines bearing a 4‐benzyloxyanilino tail ( 5a–h and 8a–h ) were synthesized via pathways outlined in Schemes . The synthesis of the corresponding key intermediates ( 2a–h ) depending on using of Williamson ether synthesis which was accomplished by stirring of p ‐nitrophenol in dimethylformamide with the appropriate benzyl bromide derivatives to afford the nitro derivatives in higher yields and high purity ( 1a–h ) . 4‐Benzyloxyanilines were synthesized through reduction of their corresponding nitro derivatives using Fe powder in NH 4 Cl and 70% ethanol (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the corresponding key intermediates ( 2a–h ) depending on using of Williamson ether synthesis which was accomplished by stirring of p ‐nitrophenol in dimethylformamide with the appropriate benzyl bromide derivatives to afford the nitro derivatives in higher yields and high purity ( 1a–h ) . 4‐Benzyloxyanilines were synthesized through reduction of their corresponding nitro derivatives using Fe powder in NH 4 Cl and 70% ethanol (Scheme ). The reaction of ethyl acetoacetate, malononitrile, sulphur powder, and morpholine in water bath in a one pot procedure following Gewald procedures afforded the methyl 2‐amino‐3‐cyanothiophene‐5‐carboxylate precursor ( 3 ) in good yield and melting point as reported .…”
Section: Resultsmentioning
confidence: 99%
“…A large number of 2-aminobenzothiazole derivatives are also found to be anticancer active and the 2-aminobenzothiazole moieties act as a privileged pharmacophores as well as valuable reactive intermediates [6][7][8]. For example, N-aryl substituted 2-aminobenzothiazole (A; R116010) is a potential inhibitor of retinoic acid metabolism for cancer treatment [9]; 6-substituted 2-aminobenzothiazole (B) is found to exhibit antifungal activity [10]. Riluzole (C) is a 2-aminobenzothiazole compound employed in the treatment of amyotrophic lateral sclerosis [11] and N-disubstituted 2-aminobenzothiazole (D, HM13N) is used as anti-HIV agent [12].…”
Section: Introductionmentioning
confidence: 99%